Arctic char occurrence and abundance using environmental DNA. (2nd March 2023) - Seymour, Mathew; Smith, Antony
Abstract: Our ability to rapidly monitor species is essential for effective resource management and for establishing conservation practices. Current monitoring practices for many fish species are not effective across multiple habitats due to limited resources, permit restrictions, etc. In response, environmental DNA (eDNA)‐based surveying and monitoring programmes are increasingly being developed and applied to meet the growing demands of local regulators and resource managers. The management of Arctic char ( Salvelinus alpinus ), a fish species of economical and societal importance, is a prime candidate for eDNA surveillance as many existing and endemic populations are increasingly threatened by human activity and climate change. Here we applied and tested the effectiveness of using eDNA to survey endemic and transplanted Arctic char populations across north Wales, which represents the southern extent of the Arctic char geographic range. We used a species‐specific quantitative polymerase chain reaction (qPCR) method to assess Arctic char occurrence and estimated the biomass (e.g., abundance) of Arctic char populations for each of the sampled lakes. We found Arctic char present in four of the five lakes with eDNA detection increasing with increasing lake depth. Spatial distribution of Arctic char eDNA detection was not found to be related to spatial location or distance from inlet or outlet for each sampled lake. Arctic char biomass was estimated from eDNA using a range of previously documented eDNA concentrations to biomass measures. Following biomass validation from one lake, we suggested that a mid‐range measure of eDNA to biomass estimate (from the currently available literature) is most likely, resulting in a range of 3, 002–42, 614 g/ha for our biomass estimates across all sites. Environmental DNA sampling is an effective method for assessing Arctic char populations and offers an informative base for estimating population densities. DNA detection was not spatially structured, which might indicate that the transport dynamics of eDNA are more unpredictable than previously anticipated and that standard sampling strategies should employ spatial sampling in their design to ensure adequate detection is obtained from eDNA collection efforts. With the increasing infeasibility of traditional sampling and surveying methods it is essential to continue to test and refine our eDNA capabilities. These findings highlight the usability and sampling design strategy needed for eDNA based surveying of known and unknown locations for endemic species. We also provide an initial cross‐study framework for estimating fish abundances from eDNA data that uses and builds on existing knowledge and trends in contrast to study or site‐specific assessments.